2018
DOI: 10.2147/ndt.s192891
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure, reliability and validity of the Chinese version of the Van Dream Anxiety Scale

Abstract: Background/purposeDream emotions and contents are associated with psychological well-being. Dream disturbances, such as frequent nightmares and dream anxiety, are associated with a variety of psychopathological conditions. Therefore, it is important to consider nightmares and the resulting dream anxiety. To address this issue, the Van Dream Anxiety Scale (VDAS) was designed especially for measuring nightmare frequency and dream anxiety caused by frightening dreams. As a Chinese version of VDAS may be helpful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…On February 10, 2020, we used the Hospital Anxiety and Depression Scale (HADS), 2 the Van Dream Anxiety Scale (VDAS), 3 and Ocular Surface Disease Index (OSDI) 4 to conduct questionnaire survey via WeChat, a messaging and social media app. This study was carried out according to the Declaration of Helsinki, 5 and the plan was approved by the ethics committee of the First Affiliated Hospital of Nanchang University.…”
Section: Methodsmentioning
confidence: 99%
“…On February 10, 2020, we used the Hospital Anxiety and Depression Scale (HADS), 2 the Van Dream Anxiety Scale (VDAS), 3 and Ocular Surface Disease Index (OSDI) 4 to conduct questionnaire survey via WeChat, a messaging and social media app. This study was carried out according to the Declaration of Helsinki, 5 and the plan was approved by the ethics committee of the First Affiliated Hospital of Nanchang University.…”
Section: Methodsmentioning
confidence: 99%
“…Test anxiety was assessed through Test Anxiety Scale developed by Sarason (1978) and later revised by Wang (2001). This scale consists of 37 self‐statements concerning their mental feelings and physical discomfort before and after exams.…”
Section: Methodsmentioning
confidence: 99%
“…Test-retest reliabilities of between .80 and .87 have been reported (Sarason, 1978). The Chinese version of TAS was originally translated by C. Wang (2001), and a recent research demonstrated that the internal consistency of Chinese version TAS was .87 and test-retest reliability was .59 in Chinese high school students (Song & Zhang, 2008). In the current study the internal consistency reliability of the scale was .85 at T1, and .86 at T2.…”
Section: Methodsmentioning
confidence: 99%